COMPARISON OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS IN HEALTHY COMMUNITY HOSPITAL VISITORS[CA-MRSA] AND HOSPITAL STAFF [HA-MRSA] - Nirmal A Pathare; Anil Pathare (Mediterranean Journal of Hematology and Infectious Diseases)
Background: The prevalence of community associated methicillin resistant Staphylococcus aureus [CA-MRSA] in unknown in Oman.